2023
DOI: 10.1021/acs.jpcc.3c00005
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Adsorbate Interactions Modulate Plasmonic Reactivity of Chemisorbed Nitrophenyl Derivatives

Abstract: Energetic hot electrons generated upon nonradiative decay of localized plasmons in metallic nanostructures can be effectively harnessed to catalyze photochemical transformations of molecular adsorbates through unique reaction pathways. When designing metal− adsorbate hybrid systems for hot electron-driven photocatalysis, both the intrinsic plasmonic properties of metallic photocatalysts and the chemical nature of metal−adsorbate interactions should be taken into careful considerations. In this work, we show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…For example, the ability of a molecular adsorbate to capture hot electrons sensitively depends on the nature and strength of the molecule–metal bond and the alignment of electronic energy levels of the metal and molecule. Chen and Wang show this for plasmon-induced reductive coupling of para -substituted nitrophenyl derivatives as they vary the chemical linker group that anchors the molecules on the Ag NP surface.…”
Section: Hot-electron Transport Across Heterostructuresmentioning
confidence: 94%
“…For example, the ability of a molecular adsorbate to capture hot electrons sensitively depends on the nature and strength of the molecule–metal bond and the alignment of electronic energy levels of the metal and molecule. Chen and Wang show this for plasmon-induced reductive coupling of para -substituted nitrophenyl derivatives as they vary the chemical linker group that anchors the molecules on the Ag NP surface.…”
Section: Hot-electron Transport Across Heterostructuresmentioning
confidence: 94%
“…The critical role of the metal–molecule interfaces in plasmon-induced chemical reactions has also been highlighted in other molecular systems. The reactivity of nitrophenyl derivative adsorbates on Ag surfaces was changed by bonding modes in the metal–adsorbate interactions: σ-donation and π-back-donation …”
Section: Surface and Interfacementioning
confidence: 99%
“…The reactivity of nitrophenyl derivative adsorbates on Ag surfaces was changed by bonding modes in the metal−adsorbate interactions: σ-donation and πback-donation. 71 The importance of metal−molecule interfaces has been gradually recognized, and the contribution of interfaces to molecular excitation by plasmons has recently been investigated not only in macroscopic studies but also in microscopic and theoretical studies. Recent microscopic studies have shown that the interfacial electronic structures formed by orbital hybridization between metal surfaces and molecules affect molecular excitation by plasmons.…”
Section: ■ Surface and Interfacementioning
confidence: 99%